A hybrid nanocomposite of CeO2–ZnO–chitosan as an enhanced sensing platform for highly sensitive voltammetric determination of paracetamol and its degradation product p-aminophenol. Issue 28 (21st May 2019) - Almandil, Noor B.; Ibrahim, Mohamed; Ibrahim, Hossieny; Kawde, Abdel-Nasser; Shehatta, Ibrahim; Akhtar, Sultan
Abstract : A highly selective electrochemical sensor was fabricated based on CeO2 –ZnO–chitosan hybrid nanocomposite modified electrode and was successfully applied for the determination of PAR in pharmaceutical formulations. Abstract : For the determination of paracetamol (PAR) and its primary degradation product ( p -aminophenol, PAP) a highly selective electrochemical sensor was fabricated. A glassy carbon microspheres paste electrode (GCMPE) was modified with a CeO2 –ZnO–chitosan hybrid nanocomposite (CeO2 –ZnO–CS) which was characterized by X-ray diffraction and transmission electron microscopy. The CeO2 –ZnO–CS/GCMPE was characterized by scanning electron microscopy, and cyclic voltammetry. The modified GCMPE exhibits excellent electrocatalytic activity for the determination of PAR and PAP separately or simultaneously, typically at working potentials of 0.38 and 0.09 V vs. Ag/AgCl. The square wave voltammetric response in solutions of near-neutral pH value increases linearly in the 20 nM to 1.8 μM PAR concentration range, and the lower LOD is 0.86 nM. The sensor is shown to enable the determination of PAR even in the presence of a 180-fold excess of PAP. PAR and PAP can also be simultaneously determined, and the LODs for PAR and PAP are 0.98 nM and 9.5 nM, respectively. The results agreed well with data obtained using other electrodes. The sensor is reproducible and stable over eight weeks, and interference by biologically essential compounds is negligible. The method was applied to the determination of PAR in pharmaceutical formulations and in spiked blood serum and urine samples. The relative standard deviations ranged from 97.5 to 102.0%.